DINAMIKA PERKEMBANGAN GEREJA KRISTEN SUMATERA BAGIAN SELATAN (GKSBS) METRO SEJAK KOLONISASI HINGGA ORDE BARU - Theresia Yulindasari; Kuswono Kuswono (Swarnadwipa, 2018)
The purpose of this study is to describe the entry of Christianity in Metro, analyze the development of GKSBS Metro before independence, the beginning of independence, the Old Order until the New Order. This study uses the historical method, data collection techniques using heuristic steps (data collection), verification that includes external and internal criticism, interpretation (interpretation) and historiography (historical writing). This study uses the study books as the main source. As a support to strengthen the data collecting then also conducted an interview with the active minister GKSBS Metro, one of the Metro congregation and one of the pastor emeritus GKSBS Metro.The results of this study, GKSBS Metro is a regional church which was originally founded by the Synod GKJ Central Java. The formation of reunions in Southern Sumatra was a struggle of transmigrants who yearned for fellowship. Synod of GKJ Central Java as the pioneer sent a messenger of the messengers to serve Lampung region. Since colonization until the New Order even until now, GKSBS Metro has undergone several times the change of pastor. GKSBS has participated in health, education and social fields to serve the general public. GKSBS synod is the result of the session XVIII, August 6, 1987 decides GKJ Regional Synod l in South Sumatra declared independently and became its own synod with the name Christian Church of South Sumatra (GKSBS).